O CONSELHO DO FUNDEB E O DIREITO À EDUCAÇÃO - Silva, Flavia Marcia Costa (2021)
Fundeb is the main resource made available for financing basic education in Brazilian municipalities, with the aim of universalizing the supply of education in the country. Since its creation in 2006 and regulation in 2007, were also created as a social control strategy the CACS/Fundeb in each federated entity, whose composition brings together representatives from various segments related to education with the function of supervising the management of Fundeb’s resources. The main idea of this research is to analyze the role of Fundeb’s Monitoring and Social Control Council-CACS, in two municipalities in the state of Espírito Santo and its perspectives of contributing to the construction and implementation of democratizing educational public policies in promoting the right to education. To achieve this goal, a qualitative research was used, using document analysis, interviews and observation. As a theoretical contribution, it was based on the contributions of Chauí (1997) to the basic concepts of Democracy, Araújo (2020), Cury (2007) and Paro (2007) on Democratic Management, Peixoto (2015) on Participatory Democracy, Gohn (1994, 2007, 2006) on Participation and on councils and public management, Cury (1996) on Financing, Davies (2015) on Council for Monitoring and Social Control. To obtain the data for analysis, a questionnaire was applied using the Google Forms model to identify the profile of the councilors of the surveyed Cacs, a strategy found to carry out the survey during the pandemic period. The questionnaire was organized into four axes: representation profile, education, infrastructure and role of the counselor on the board. Several weaknesses were found that hinder the effective performance of the councilors: infrastructure for the functioning of the council; lack of training and technical knowledge to perform; commitment and responsiveness to the board. As a proposal to minimize these weaknesses, we indicate the application of training for councilors, which application we expect will become concrete.